2010
DOI: 10.1007/s11127-010-9709-3
|View full text |Cite
|
Sign up to set email alerts
|

Competition among officials and the abuse of power

Abstract: Corruption, Competition, H1, K4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…5 Whether corruption persists in the long-run is open to some debate in the literature. For example, whilst RoseAckerman (1978) and Shleifer and Vishny (1993) argue that competition among officials reduces corruption to zero, this outcome depends on how powerful the central authority is (Priks 2012). public officials. The policy effort could thus be directed at identifying and monitoring interactions between public officials and the victims of the economic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Whether corruption persists in the long-run is open to some debate in the literature. For example, whilst RoseAckerman (1978) and Shleifer and Vishny (1993) argue that competition among officials reduces corruption to zero, this outcome depends on how powerful the central authority is (Priks 2012). public officials. The policy effort could thus be directed at identifying and monitoring interactions between public officials and the victims of the economic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…This paper develops a simple model to examine the effects on the severity of corruption when bribe takers or bribe givers initiate corrupt deals. While the extant literature has largely focused on the prevalence of corruption (e.g., Priks, 2012;Svensson, 2005), rather than its severity, these scenarios are consistent with collusion among bribe takers and bribe givers and with extortion by bureaucrats (Ahlin and Bose, 2007;Mishra, 2006; Rose-Ackerman, 2010; Shleifer and Vishny, 1993;. For instance, the first mover in corrupt relations might emerge due to numerous factors including the relative discount rates of the two parties, relative bargaining positions, degree of competition, socio-cultural norms, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In practice a series of bribes might have to be paid to accomplish one corrupt deal. 14 In different settings, Bliss and Di Tella (1997) and Priks (2012) have shown that greater competition might not necessarily lower corruption. 15 As a practical matter, however, this elasticity may be difficult to observe for enforcement bodies, although one can expect the elasticity to change when bureaucrats face the end of their tenures, voluntarily or otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The "accountability black hole" describes the concentration of societal accountabilities in the government, which struggles with the complexity of public problems, leading to declining public trust. This issue is exacerbated by governments' competition to gain more authority and power (Priks, 2012), and the public's unrealistic expectations of government capabilities (Hibbing and Theiss-Morse, 2002;Putnam et al, 2000). As a result, governments face challenges such as the complexity of issues (Kalesnikaite and Neshkova, 2021;Noto et al, 2023), the helplessness of citizens or corporations in addressing these problems (Head, 2023;Reinecke and Ansari, 2016), and the difficulty of managing intersectoral networks (Scott and Thomas, 2017;Sowa and Lu, 2017).…”
Section: Basis Of the Collaborative Accountability Frameworkmentioning
confidence: 99%